Exploring intraspecific variation in salinity tolerance at germination and seedling development stages in Camelina sativa - Mastroberardino, Rossella; Zanetti, Federica; Monti, Andrea (Frontiers in Plant Science, 2025)
IntroductionCamelina sativa is a promising oilseed crop for cultivation on saline marginal lands due to its abiotic stress tolerance and low input requirements. However, intraspecific variation in salinity tolerance remains poorly understood.MethodsThis study, through three sequential experiments, applied a screening framework integrating time-to-event modeling, stress tolerance indices (STIs), and multivariate clustering to dissect variation in salinity tolerance across early developmental stages. In experiment 1, two commercial varieties were germinated under a gradient from 0 to 300 mM of NaCl. In experiment 2, 57 camelina accessions were evaluated at 0 and 200 mM of NaCl for six germination indices (total germination, germination index, mean germination time, velocity coefficient, synchronization index, and normality rate) expressed as STIs, to quantify relative performance under salinity. In experiment 3, 13 representative accessions were assessed for seedling STIs (shoot length, main root length, lateral root length) under 0 and 200 mM of NaCl.Results and discussionTime-to-event analysis revealed significant varietal differences in germination dynamics, with 200 mM identified as the optimal threshold for discriminating genotypic responses without complete germination inhibition. Most accessions retained ≥90% total germination under salinity, yet principal component analysis and hierarchical k-means clustering classified them into three phenotypic groups with distinct germination strategies. Salinity strongly reduced lateral root length (−90%), main root length (−80%), and shoot length (−30%), indicating altered biomass allocation in response to salt stress. Integration of germination clusters with seedling responses revealed three adaptive strategies: 1) high but delayed germination accompanied by strong seedling vigor, 2) low germination with intermediate seedling tolerance, and 3) high and rapid germination accompanied by poor seedling growth.ConclusionsThese findings highlight salinity tolerance as a stage-dependent trait, underscoring the need for multistage phenotyping to guide breeding of C. sativa for saline environments.